Importance of community participation for placemaking - Wee, Ji Quan (2022)
The research aimed to outline the importance of community participation in a placemaking process. Placemaking is implying human attachment to places that are appealing and fit for their intended uses. Placemaking stresses the importance of community participation and decision-making, this type of engagement builds an important link and attachment between the people and the area where they reside. Despite the understand of the need of public participation, many placemaking process still use a top-down or expert-driven decision making in the process. The research has noted that the public participation in an urban planning and decision making in general can maximize the satisfaction with planning outcomes, project lifespan and possibilities for increasing civic engagement and interest. Some of the researchers also highlighted to the planners to actively involve the local community to recognise the people’s right to the city from the beginning. In order to support the research statements, 3 case studies were carried out in the Kuala Lumpur and Penang Island context. The selected case studies were made with comparison with different initiative party and community engagement process. The case study comparison outlined the importance of community engagement during the placemaking process. Placemaking project that had engaged with the local community has resulted to be more sustainable in the long run.